Effect of Spacing on Stem and Crown Development in Cottonwood (Populus deltoides Bartr.) - Mishraand N. K., V. K. (Indian Forester, 1993)
Spacing showed significant effect on various stem and crown parameters excepting degree of crown spread in 7 year old plantation of Populus deltoides. Height, dbh, basal area and stem volume responded positively to spacing whereas hole length declined. Among the crown characteristics i.e. crown length, crown diameter, crown basal area, crown surface area, crown volume and live crown ratio improved with increase in spacing whilst crown projection ratio decreased. Significant positive correlations were observed between crown surface area and crown volume, stem volume and crown volume, stem volume and crown surface area, stem basal area and crown volume, stem basal area and crown surface area, stem diameter and live crown ratio, and crown diameter and stem diameter.